Building resilient organizations through change, chance, and complexity - Lindstedt, David (New York, NY : Routledge, 2022)
A must-read in the wake of COVID-19, this book unpacks the nature of resilient organizations and how they prepare for unpredictable, complex, and profound change. Organizations that do not adapt and evolve die. To date, however, it has not been at all clear how to build a resilient organization. That puts us all in the unenviable position of trying to ready our organizations for an increasingly uncertain future without the proper guidance to do it. This book introduces 14 elements of resilience that consistently emerge in organizations that have thrived amid adversity and volatility. Resilience is not about determination, grit, cybersecurity, or teams of resilient individuals; resilience, it turns out, is often confused with robustness. Readers will discover how resilient organizations build and employ a distinctive combination of crews, capital, culture, and leadership--and, crucially--how to adapt these combinations for their own organization. Senior business leaders, consultants, entrepreneurs, students, and professionals will appreciate this book's practical, approachable, and engaging guidance, including insights by leaders from Health Care for the Homeless, The Ohio State University, NBCUniversal, retail stores, and more.
Keywords: BUSINESS & ECONOMICS / Leadership; BUSINESS & ECONOMICS / Strategic Planning; Organizational change; Business planning; Diversity in the workplace -- Management; Leadership